Tracking young talented swimmers: follow-up of performance and its biomechanical determinant factors - Morais, Jorge (2020)
The aim of the study was to follow-up the stability of young talented swimmers' performance and its biomechanical determinant factors (i.e., anthropometrics, kinematics, hydrodynamics and efficiency) during a competitive season. Thirty three (15 boys and 18 girls) young swimmers (overall: 11.81 ± 0.75 years old and Tanner stages 1-2 by self-evaluation) were evaluated. Performance, anthropometrics, hydrodynamics, kinematics and efficiency variables were assessed at three moments during a competitive season. Performance had a significant improvement (with minimum effect size) and a moderate-very high stability throughout the season. In the anthropometrics domain all variables increased significantly (ranging from without to minimum effect size) between moments and had a moderate-very high stability. Hydrodynamics presented no variations between all moments and had a low-very high stability throughout the season. In the kinematics domain, there were no variations between moment one and three, except for an increase in stroke frequency (without size effect). Speed fluctuation remained constant, with no significant variations. All kinematic variables had a low-very high stability. Efficiency variables did not present variations between moment one and three and had a low-moderate stability. Overall, young swimmers showed a minimum improvement in performance and in anthropometric factors; and a moderate stability of performance and its determinant factors (i.e., anthropometrics, hydrodynamics, kinematics and efficiency) during the competitive season.